Nikon D90 digital field guide - Thomas, J. Dennis (Wiley Pub., 2009)
Capture spectacular images, even video, with your D90. Your Nikon D90 is simply revolutionary -- the first dSLR that also lets you shoot live HD video straight from the image sensor by using Live View. With so much to know about this remarkable camera, you'll want to take this book along on every shoot. It covers all the settings, modes, and menus; explores the applications for every available lens; guides you through lighting essentials; and provides advice for capturing great still and video images in a dozen situations.:. Learn to compose your photos with the LCD monitor for clear, vibrant s.